MODIFICATION OF MECHANICAL EQUIPMENT SEMI corn sheller - Nurdin - Ar Rasid (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2014)
The purpose of this research is to improve the performance of the tool before and get a corn sheller sheller corresponding cylindrical shape. The modified part was the cylinder of sheller by using 4, 8, and 12 segments of serrations. Each cylinder received 3 treatments. The cylinder was fed by 1 cob (T1), 2 cobs (T2), and 3 cobs (T3) with three replications. This research was successful to modify the corn sheller machine with dimension of 100 cm x 50 cm x 115 cm with three types of sheller cylinders. The mechanism principle of this corn sheller was that the sheller cylinder in the middle of holder cylinder was operated by human power through hand crank with 50 to 70 rpm. The results showed that the highest yield (96%) was obtained by corn sheller with 4 serrations while 4% remained unshelled. The lowest yield (92%) was obtained by corn sheller with 12 serrations while 8% remained unshelled. From all treatments, the best result was corns sheller with 4 serrations fed with 3 corn cobs with percentage of 99.40% good shelled weight and 0.60% poor shelled. The lowest result with biggest damage was in the corn sheller with 8 serrations fed with 1 corn cob. The result was 97.53% good shelled and 2.47% poor shelled. The highest capacity (1.58 kg corn cobs/minute) was obtained by the corn sheller machine with 4 serrations.Keyword: Corn sheller, modification cylinder sheller, performance tools